The Effects of Nanoparticle Addition in Bi-2212 Superconductors (Jurnal Teknologi (Sciences & Engineering), 2014)
The effect of Y2O3 nanoparticle addition on the superconducting properties of Bi1.6Pb0.4Sr 2CaCu 2Oy have been investigated. The samples were prepared using high purity oxide powders via solid state reaction method. Y2O3 nanoparticle with 0.0-1.0 wt. % was systematically added to the well balanced Bi1.6Pb0.4 Sr2CaCu2Oy before sinter in order to trace the existense of nanoparticle addition in the system. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and critical current density, Jc. The current density measurement was done via four-point probe method under zero magnetic fields. The critical current density, Jc and superconductivity transition temperature, Tc for sample with addition of Y2O3 nanoparticle were found to be higher than the pure sample. The optimal addition of Y2O3 nanoparticle to the sample Bi-2212 system was found at 0.7 wt. %. The crystallographic structure of all samples was evidenced to be orthorhombic where a â‰  b â‰  c. Changes in superconducting properties of Y2O3 nanoparticle added Bi-2212 system were discussed.